Enhanced thermal conductivity of epoxy acrylate/h‐BN and AlN composites by photo‐curing 3D printing technology. Issue 29 (16th May 2022) - Lin, Yucong; Deng, Weijian; Rui, Yueyue; Liu, Yun; Lu, Gang; Liu, Jie
Abstract: Filling hexagonal boron nitride (h‐BN) is a hot topic in the research of improving the thermal conductivity of polymer composites. Conversely, its difficulty in dispersing and forming a three‐dimensional thermal network has become a major problem. This article uses liquid resin can effectively help the filler to be evenly dispersed and construct a multi‐layer connection network through 3D printing technology, which improves the thermal conductivity of polymer effectively. With the addition of 30 wt% h‐BN, the thermal conductivity of the epoxy acrylate (EA) composite reaches 1.60 Wm −1  K −1, which is 6.8 times that of pure epoxy acrylic resin. Our work provides a new idea for improving the thermal conductivity of photocured polymers. Abstract : Photosensitive resin and DLP 3D printing method are used to prepare h‐BN/epoxy acrylate (EA) and h‐BN/AlN/EA thermal conductive polymer. Using liquid resin can help fillers to be evenly dispersed, and then create a multi‐layer connection network through 3D printing technology, which improves the thermal conductivity of polymer effectively.